Art and reification: Georg Lukacs' critique on Brecht. Issue 2 (3rd July 2022) - Potamias, Spyros; Mandilara, Iro
Abstract : In this article, we intend to combine the few and short passages where Georg Lukacs exerts his criticism on Bertolt Brecht's dialectical theatre with the Lukacsian aesthetic theory as a whole, in order to comprehend and designate those points, on which the above-mentioned criticism is based. Both thinkers' main concern was to discover ways in which art could contribute to the overcoming of the reification phenomenon. However, since they perceive reification differently, they deal with art's de-reificating role differently too, at least until the end of 1930s. Therefore, in this article, through the discourse and the critical evaluation of these divergencies, we aim to give prominence both to the foundation of the Lukacsian critique on Brecht and the convergencies that are detected from the 1930s onwards.